Pengaruh Penerapan Pembelajaran Discovery Strategy Terhadap Hasil Belajar Kognitif Pada Mata Pelajaran TIK Siswa Kelas XI (studi kasus: SMAN 1 Gianyar Tahun Ajaran 2012/2013) - Anak Agung Sri Farida Sari Dewi; Luh Putu Eka Damayanthi; Dessy Seri Wahyuni; I Made Gede Sunarya (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
This study aimed to find out whether there was a significant difference toward cognitive learning achievement in Information Technology (ICT) subject between groups of students who were taught using Discovery Learning Strategy and those who were taught using conventional strategy. This study was categorized into pseudo experiment (quasi experiment) in which Control Grup Design was used as research design in this study. The population of this research was eleventh grade students of SMA 1 Gianyar in the academic year 2012/2013. The sample of this study was the eleventh grade of science class 4 eleventh grade of science class 6 with the total number of sample was 64. The eleventh grade of science class 4 was used as the experiment class while the eleventh grade of science class 6 was used as the control class. Multiple choices test was used as the data collection to measure the students’ cognitive aspect. Precondition test was conducted to analyze the data including normality testing and homogeneity testing and hypothesis testing in the form of T Relating to the result of the analys found that the normality and the homogeneity of both groups were normally and homogeneity distributed. The average score of the group of students who were taught using discovery learning strategy was higher than the group of students who were ta direct learning strategy.The result of the analysis showed that tcalculation > ttable, the implementation of discovery learning strategy influenced significantly toward cognitive learning achievement in ICT subject for the eleventh grade students of science class of SMA 1 Gianyar in the academic year 2012/2013.